2011
DOI: 10.1182/blood-2010-04-280750
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoiesis and leukemogenesis in mice expressing oncogenic NrasG12D from the endogenous locus

Abstract: NRAS is frequently mutated in hematologic malignancies. We generated Mx1-Cre, Lox-STOP-Lox (LSL) -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
151
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(161 citation statements)
references
References 45 publications
(68 reference statements)
9
151
1
Order By: Relevance
“…8 The Mx1-Cre system has been used to induce a latent Nras LSL-G12D "knock-in" allele in mice resulting in both MPD and a polyclonal lymphoproliferative disorder (LPD). 9 Together, these studies-showing that endogenous K-Ras G12D and N-Ras G12D protein expression perturbs myeloid and lymphoid growth control-are consistent with the discovery of NRAS and KRAS mutations in patients with LPD.…”
Section: Oncogenic Ras Scales the Alps ------------------------------supporting
confidence: 50%
See 1 more Smart Citation
“…8 The Mx1-Cre system has been used to induce a latent Nras LSL-G12D "knock-in" allele in mice resulting in both MPD and a polyclonal lymphoproliferative disorder (LPD). 9 Together, these studies-showing that endogenous K-Ras G12D and N-Ras G12D protein expression perturbs myeloid and lymphoid growth control-are consistent with the discovery of NRAS and KRAS mutations in patients with LPD.…”
Section: Oncogenic Ras Scales the Alps ------------------------------supporting
confidence: 50%
“…In mice, genetic background strongly modulates the disease phenotype with LPD more prominent in the inbred C57Bl/6 strain. 8,9 Modifier loci could also exist in humans. Differences in the cell type in which the inciting mutations occur and/or in the nature of any cooperating mutations could determine whether a patient develops RALD, JMML, or another hematologic disease.…”
Section: Oncogenic Ras Scales the Alps ------------------------------mentioning
confidence: 99%
“…Similarly, Nras G12D KI mice harbor a wide spectrum of myeloid diseases with a highly penetrant CMML in bone marrow transplantation assays. 2,3 However, none of these models develop AML, suggesting that other associated genetic or epigenetic events are necessary to induce a full-blown leukemia.…”
Section: William Vainchenker and Isabelle Plo Insermmentioning
confidence: 99%
“…We and others previously reported that bone marrow cells from Nras G12D/ϩ mice form a significant number of colonies in the absence of cytokines (10,11). To determine whether the spontaneous colony formation of Nras G12D/ϩ cells depends on ␤c-mediated signaling, we isolated bone marrow cells from control, Nras G12D/ϩ , and Nras G12D/ϩ ; ␤c Ϫ/Ϫ mice and plated them in semi-solid medium in the absence of cytokines.…”
Section: Loss Of ␤C Abolishes Oncogenic Nras-induced Spontaneousmentioning
confidence: 99%